"What about FH of my child?" parents' opinion on family history collection in preventive primary pediatric care. (August 2015) - Syurina, Elena V; Gerritsen, Anne-Marie JM; Hens, Kristien; Feron, Frans JM
Objective : Family history (FH) in Preventive Primary Pediatric Care is to identify children at risk for complex diseases and provide personal preventive strategies. This study was to assess parents' opinion on FH collection.Methods : Semi-structured interviews were conducted. Among issues addressed were: former experiences with FH, knowledge about FH, family definition and sharing information about FH.Results : The importance of FH for participants depended on their knowledge, perceived family health status and former experiences. After insight into FH, parents shift to believing it to be important, but certain barriers exist in reporting FH.Conclusion : Parents suggest that the importance of FH should be more emphasized and more trusting relationship with Preventive Primary Pediatric Care should be invested in.